2022 IJSPT Orthopedic Summit Research Abstracts - International Journal of Sports Physical Therapy (International Journal of Sports Physical Therapy)
The International Journal of Sports Physical Therapy is pleased to publish abstracts from the 12th Orthopaedic Summit (OSET) taking place in Boston, September 21-24, 2022. The IJSPT hosted the 2nd annual research forum and reception at OSET, sponsored by ATI Physical Therapy and Hyperice.